Combination of venetoclax and azacitidine in relapsed/refractory acute B-cell lymphoblastic leukemia: a case series from a single center - Ziyi Hao; Yingying Fei; Juan Chen; Sailan Huang; Li Wang; Youhuan Yu; Meiru Bian; Yejun Si; Xingxia Zhang; Xiaotian Yang; Bing Zhang; Yan Wan; et al. (Hematology)
Objectives: Relapsed/refractory acute B-cell lymphoblastic leukemia (R/R B-ALL) often responds poorly to induction chemotherapy. However, recent research has shown a novel and effective drug treatment for R/R B-ALL.Methods: A total of eight patients with R/R B-ALL were enrolled in the study from November 2021 to August 2022. All patients received chemotherapy based on a combination regimen of venetoclax and azacitidine. The regimen was as follows venetoclax 100 mg d1, 200 mg d2, 400 mg d3–14, azacitidine 75 mg/m2 d1–7.Results: Five of eight patients achieved very deep and complete remission (CR) with minimal residual disease (MRD) less than 0.1%. One patient achieved partial remission. Two patients did not achieve remission. There were no serious adverse events and all patients were well tolerated. Three patients were eligible for consolidation chemotherapy and were bridged to CAR-T therapy.Conclusions: The combined regimen of venetoclax and azacitidine may be beneficial for patients with R/R B-ALL.